Long Noncoding RNAs as Orchestrators of CD4+ T-Cell Fate - Liu, Chang; Zhang, Yanli; Ma, Zhanchuan; Yi, Huanfa (Frontiers in Cell and Developmental Biology, 2022)
CD4+ T cells differentiate towards different subpopulations through the regulation of lineage-specific cytokines and transcription factors, which flexibly respond to various immune challenges. However, considerable work has demonstrated that the CD4+ T-cell differentiation mechanism is complex and not limited to transcription factors and cytokines. Long noncoding RNAs (lncRNAs) are RNA molecules with lengths exceeding 200 base pairs that regulate various biological processes and genes. LncRNAs have been found to conciliate the plasticity of CD4+ T-cell differentiation. Then, we focused on lncRNAs involved in CD4+ T-cell differentiation and enlisted some molecular thought into the plasticity and functional heterogeneity of CD4+ T cells. Furthermore, elucidating how lncRNAs modulate CD4+ T-cell differentiation in disparate immune diseases may provide a basis for the pathological mechanism of immune-mediated diseases.